Kuntai Capsule Combined With Letrozole on Gonadal Hormone Levels and Ovarian Function in Patients With PCOS: A Systematic Review and Meta-Analysis - Tang, Xing; Huang, Qinwan; Wang, Chengcheng; Zhang, Da; Dong, Shoujin; Yu, Congcong (Frontiers in Endocrinology, 2021)
Abstract Background: The efficacy of Kuntai capsule combined with letrozole in improving ovarian function of PCOS has been evaluated before, but there is still a lack of evidence-based evidence to support the regulation of sex hormone levels. In recent years, new RCTs have been reported on the effect of combined therapy on regulating sex hormone levels. Objective: To systematically evaluate the efficacy of Kuntai capsule combined with letrozole (LE) in the treatment of polycystic ovary syndrome (PCOS). Methods: A search across CBM、CNKI, VIP database, Wangfang database, PubMed, Web Of Science, The Cochrane Library and Embase was conducted on Kuntai capsule combined with letrozole in the treatment of PCOS, the time of self-built database was up to April 30, 2021. Randomized controlled clinical trials of letrozole (LE) in the control group and letrozole combined with Kuntai capsule in the experimental group were selected. RevMan5.3 software was used for data analysis. Results: A total of 17 literatures were included, including 1684 patients. Meta-analysis results showed that the total effective rate of the combined group was 93.36%, and the total effective rate of the LE group was 78.15%. The improvement of ovulation rate, pregnancy rate, number of mature follicles, endometrial thickness, cervical mucus score and serum follicle stimulating hormone (FSH), luteinizing hormone (LH) and prolactin (PRL) in the combined group was consistent with the results of previous Meta analysis, and was better than that in the LE group (P<0.05).In addition, the combination group was better than LE group in regulating the levels of estradiol (E2) and testosterone (T) (P<0.05). There were no adverse drug reactions in the two groups during treatment. Conclusion: As a kind of pure traditional Chinese medicine preparation, Kuntai capsule combined with letrozole has a better effect than letrozole alone in the treatment of PCOS, with advantages mainly reflected in enhancing ovarian function and regulating the level of sex hormones in vivo, etc., but the value of combined therapy still needs to be verified by more high-quality randomized clinical trials.